2023
DOI: 10.1155/2023/5142965
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy Evaluation of Standardized Precipitation Index (SPI) Estimation under Conventional Assumption in Yeşilırmak, Kızılırmak, and Konya Closed Basins, Turkey

Mehmet Ali Hinis,
Mehmet Selim Geyikli

Abstract: The doubt in the calculation algorithm of the standardized precipitation index (SPI), which is widely preferred in the evaluation and monitoring of drought, still remains up-to-date because its calculation process is performed in the form of standardization or normalization with a default probability distribution. Therefore, the success of this index is directly affected by the choice of the probability distribution model. This study is based on the effect of three different parameter estimation methods on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The KB is the second largest basin of the country with a drainage area of 82 221 km 2 where about 4 million people reside in 18 provinces (FMP, 2019). The basin receives an estimated precipitation of 455 mm per annum with an air temperature of 13.7°C (Hinis & Geyikli, 2023). There are six sub‐basins in the basin, including the Upper Kizilirmak Basin (UKB), Lower Kizilirmak Basin (LKB), Central Kizilirmak Basin (CKB), Delice Basin (DB), Seyfe Closed Basin (SCB), and Develi Closed Basin (DCB) (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…The KB is the second largest basin of the country with a drainage area of 82 221 km 2 where about 4 million people reside in 18 provinces (FMP, 2019). The basin receives an estimated precipitation of 455 mm per annum with an air temperature of 13.7°C (Hinis & Geyikli, 2023). There are six sub‐basins in the basin, including the Upper Kizilirmak Basin (UKB), Lower Kizilirmak Basin (LKB), Central Kizilirmak Basin (CKB), Delice Basin (DB), Seyfe Closed Basin (SCB), and Develi Closed Basin (DCB) (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…It has been conducted by scientist to identify many droughts in terms of various region. For example, Hinis and Geyikli, (2023) discussed the accuracy of SPI predictions using several candidate distributions in Yeşilırmak, Kızılırmak and Konya Closed Basins. They revealed that L-moments for 3month series and maximum likelihood approaches for 12-month series were most strong.…”
Section: Introductionmentioning
confidence: 99%